Household expenditure on leprosy outpatient services in the Indian health system: A comparative study. - Anuj Tiwari; Pramilesh Suryawanshi; Akash Raikwar; Mohammad Arif; Jan Hendrik Richardus (Public Library of Science (PLoS), 2018)
Leprosy is a major public health problem in many low and middle income countries, especially in India, and contributes considerably to the global burden of the disease. Leprosy and poverty are closely associated, and therefore the economic burden of leprosy is a concern. However, evidence on patient's expenditure is scarce. In this study, we estimate the expenditure in primary care (outpatient) by leprosy households in two different public health settings.We performed a cross-sectional study, comparing the Union Territory of Dadra and Nagar Haveli with the Umbergaon block of Valsad, Gujrat, India. A household (HH) survey was conducted between May and October, 2016. We calculated direct and indirect expenditure by zero inflated negative binomial and negative binomial regression. The sampled households were comparable on socioeconomic indicators. The mean direct expenditure was USD 6.5 (95% CI: 2.4-17.9) in Dadra and Nagar Haveli and USD 5.4 (95% CI: 3.8-7.9) per visit in Umbergaon. The mean indirect expenditure was USD 8.7 (95% CI: 7.2-10.6) in Dadra and Nagar Haveli and USD 12.4 (95% CI: 7.0-21.9) in Umbergaon. The age of the leprosy patients and type of health facilities were the major predictors of total expenditure on leprosy primary care. The higher the age, the higher the expenditure at both sites. The private facilities are more expensive than the government facilities at both sites. If the public health system is enhanced, government facilities are the first preference for patients.An enhanced public health system reduces the patient's expenditure and improves the health seeking behaviour. We recommend investing in health system strengthening to reduce the economic burden of leprosy.